ANALISIS SIKAP TOLERANSI SESAMA TEMAN SEBAYA PADA MATA PELAJARAN PPKn KELAS XI IPA SMA NEGERI 6 PONTIANAK - Dede Hendarudin; Achmadi Achmadi; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2019)
Abstract This research aims to determine the tolerance of learners towards the elderly, religious of religious and differences of opinion, and to identify the efforts of educators to promote tolerance among learners through the teaching of Civic Education. This was qualitative research on the 12th-grade science students of SMAN 6 Pontianak. The discussion of the data was presented descriptively. Research data were collected from 12th-grade science students, Civic Education and Counseling teachers at SMAN 6 Pontianak through direct observation, interviewing and documentation techniques. The results have showing that learners have well-established tolerance values, which can be seen from polite attitudes towards teachers and respect for religious differences. The students applying in differences of opinion, see from the way and polite language when expressing opinions. Efforts to provide learners with tolerance values are show by a teacher bringing an explanation and insight of tolerance through the teaching of Civic Education with the material on Unity in Diversity as part of the Pancasila values. Keywords: Qualitative Study, Tolerance, Civic Education.